2011
DOI: 10.4161/gmic.2.4.17863
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal dysbiosis in inflammatory bowel disease

Abstract: The worldwide incidence of inflammatory bowel disease (IBD) is increasing. Abundant literature has suggested that an imbalance between harmful and protective bacteria, or dysbiosis, of the intestine is largely responsible for the rising incidence of IBD. In this review, data supporting dysbiosis as a cause of IBD are presented. A comparison of the number of scientific publications in the US versus Europe on intestinal dysbiosis and microbiota revealed the US scientific community has a lower level of interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 47 publications
2
74
0
1
Order By: Relevance
“…In particular, probiotic bacteria with anti-inflammatory capabilities offer new perspectives in the context of a rising incidence of pathologies linked with dysbiosis21. The latter involves an imbalance of the gut microbiota, involving the expansion of pro-inflammatory bacteria at the expense of their anti-inflammatory counterparts22. Diet modulates the structure, diversity and metabolism of the gut microbiota2324, suggesting that these diseases could be alleviated by dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, probiotic bacteria with anti-inflammatory capabilities offer new perspectives in the context of a rising incidence of pathologies linked with dysbiosis21. The latter involves an imbalance of the gut microbiota, involving the expansion of pro-inflammatory bacteria at the expense of their anti-inflammatory counterparts22. Diet modulates the structure, diversity and metabolism of the gut microbiota2324, suggesting that these diseases could be alleviated by dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, an altered gut microbiota has long been suspected to play an important role in IBD pathogenesis. 5,6 In this context, the frequent recovery of particular strains of Escherichia coli with adherent and invasive properties [adherentinvasive E. coli, AIEC] from the mucosa of CD patients has attracted considerable attention. These bacteria constitute a new pathovar of E. coli, lacking the type III secretion system and other classical virulence factors typically associated with pathogenic intestinal E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assays have shown that this altered microbiota and some enterobacteria isolated from CD patients could activate proinflammatory pathways, while some bifidobacteria could inhibit the inflammatory or toxic effects induced by the same isolated enterobacteria and gluten peptides (21)(22)(23)(24). Alterations in the intestinal microbiota are also involved in the pathogenesis of chronic inflammatory bowel disease (IBD) (25,26) and other immune-related disorders (27)(28)(29). For instance, IBD patients have altered duodenal bacterial populations in comparison to healthy controls (30)(31)(32).…”
mentioning
confidence: 99%